DETERMINAN STRUKTUR MODAL BERDASARKAN PECKING ORDER THEORY PADA PERUSAHAAN SEKTOR BARANG KONSUMSI DI BEI - Novitayanti, Cok Istri Diah; Rahyuda, Henny (E-Jurnal Manajemen, 2018)
Capital structure is a combination of using debt and equity in the company’s for long term financial structure, it’s important for companies to consider the factors that can influence the capital structure to obatain optimal capital structure. The purpose of this research is to describe the determinant of capital structure based on pecking order theory on consumer goods sector company in Indonesia Stock Exchange year 2012-2016. The research uses associative design with quantitative approach. The method used to determine sample is non – probability sampling method with purposive sampling technique which sample size 32 companies. Data analysis technique used is multiple linear regression analysis. The result of this research indicates that, partially sales growth negative not significantlyinfluance to capital structure, liquidity negative significantly influence to capital structure, non- debt tax shield negative not significantly influence to capital structure, profitability positive significantly influence to capital structure, companies size negative significantly influence to capital structure, and tangible assets positive significantly influence to capital structure. Keyword: determinant, capital structure, pecking order theory